Children with bicytopenia and pancytopenia – clinical picture, etiological spectrum, and outcome - Vijay Anand M,; Logeshwaran K,; Srenivas A,; Sathiya Suresh R, (Asian Journal of Medical Sciences, 2024)
Background: Children who develop cytopenias present with several etiological causes, posing diagnosis, and management difficulties for both physicians and pathologists. With these in mind, we assessed the clinical profile and etiology of children who attended a healthcare facility in South India with bicytopenia or pancytopenia. Aims and Objectives: (1) The primary objective of this study was to find out the clinical and etiological spectrum in children with bicytopenia and pancytopenia who were admitted to the Institute of Child Health and Research Center, Government Rajaji Hospital, Madurai. (2) The secondary objective of this study is to follow-up children with bicytopenia and pancytopenia to find out the outcome and prognosis. Materials and Methods: This study was in the Department of Pediatrics at the Government Rajaji Hospital in Madurai, Madurai Medical College’s Institute of Child Health and Research Center, which is where we carried out the study. Two hundred and sixty-four patients with bicytopenia and 36 patients with pancytopenia were included in this study. Once in 2 weeks, all children with bicytopenia and pancytopenia were assessed in our Saturday hematology outpatient clinics. Results: Fever was the most prevalent sign of both pancytopenia and bicytopenia in this investigation. Etiological variables among cases of pancytopenia, cancer, infections, non-infections, and idiopathic causes were recorded in 11%, 58%, 17%, and 14% of cases, respectively. Similarly, bicytopenia, malignancy, infections, non-infections, and idiopathic causes were found in 23%, 70%, 4%, and 3% of cases, respectively. According to the prognosis, 28%, 33%, 6%, and 33% of cases with pancytopenia recovered, passed away, were lost to follow-up, or were undergoing treatment, respectively. Similar to those individuals, 67%, 11%, 4%, and 18% of bicytopenia cases were treated, recovered, or lost to follow-up, respectively. Conclusion: In children, there is a wide etiological range of cytopenias. Infections and dangerous diseases like acute leukemia are among the reasons. The geographical location of the hospital, the frequency of malnutrition, and the regional presence of certain diseases such as malaria and enteric fever determine the causes reported in a hospital environment.